2017
DOI: 10.1002/rse2.56
|View full text |Cite
|
Sign up to set email alerts
|

Predictive power of remote sensing versus temperature‐derived variables in modelling phenology of herbivorous insects

Abstract: Application of remote sensing datasets in modelling phenology of heterotrophic animals has received little attention. In this work, we compare the predictive power of remote sensing versus temperature-derived variables in modelling peak flight periods of herbivorous insects, as exemplified by nocturnal moths. Moth phenology observations consisted of weekly observations of five focal moth species (Orthosia gothica, Ectropis crepuscularia, Cabera exanthemata, Dysstroma citrata and Operophtera brumata) gathered i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
13
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 18 publications
(14 citation statements)
references
References 58 publications
1
13
0
Order By: Relevance
“…Insects are expected to show a tighter correlation with the spatial gradient than vertebrates, simply because the physiology and behaviour of these ectotherms are more tightly driven by changes in temperature than for endotherms (Thackeray et al, ). Our findings are supported by research on the phenology of Finnish moths for which latitudinal relationships were shown to be very variable and sometimes of poor predictive power, despite strong relationships with snow melt and leafing date: only two of the five moth species studied showed any relationship with latitude and when compared, they had opposing relationships with latitude ( Orthosia gothica positive; Operophtera brumata negative Pöyry et al, ). Clearly, even at the species level, moths have a complex relationship with space that is not easily resolvable by simple spatial terms and requires further study.…”
Section: Discussionsupporting
confidence: 79%
“…Insects are expected to show a tighter correlation with the spatial gradient than vertebrates, simply because the physiology and behaviour of these ectotherms are more tightly driven by changes in temperature than for endotherms (Thackeray et al, ). Our findings are supported by research on the phenology of Finnish moths for which latitudinal relationships were shown to be very variable and sometimes of poor predictive power, despite strong relationships with snow melt and leafing date: only two of the five moth species studied showed any relationship with latitude and when compared, they had opposing relationships with latitude ( Orthosia gothica positive; Operophtera brumata negative Pöyry et al, ). Clearly, even at the species level, moths have a complex relationship with space that is not easily resolvable by simple spatial terms and requires further study.…”
Section: Discussionsupporting
confidence: 79%
“…The lack of spatial data on ecologically relevant factors driving species distribution constraints the full potential of SDMs for management and monitoring purposes [11][12][13]. In particular, RS can provide critical information on species habitat requirements such as soil moisture (measured through e.g., normalized difference of water indices [14]), microclimatic conditions (e.g., land-surface temperature [15]) or vegetation productivity (e.g., spectral vegetation indices [16]), thus improving species niche characterization and SDMs predictions [11]. In addition, the high spatiotemporal resolution of EO data obtained from satellite sensors such as Moderate Resolution Imaging Spectroradiometer (MODIS) (from TERRA/AQUA satellites) and MultiSpectral Instrument (MSI) (from Sentinel-2 mission) allows derivation of different descriptors of ecosystem functioning (also known as remotely sensed ecosystem functioning attributes; hereafter RS-EFAs) [17,18].…”
Section: Introductionmentioning
confidence: 99%
“…O . gothica overwinters as pupae, adults emerge and oviposit in spring, and larvae feed on foliage at the start of the growing season (Figure 1 ; Elmquist et al, 2011 ; Pöyry et al, 2018 ). In contrast, P .…”
Section: Methodsmentioning
confidence: 99%